Legal Challenges of Smart Contract Integration in Indonesian Notarial Practice - Eni Arfianti; Salim HS; Ari Rahmad Hakim Budiawan Firdaus (Faculty of Law, University of Mataram, 2026)
This research aims to analyze, the legal framework required for the implementation of smart contract technology in the execution of authentic deeds and the implications of smart contract adoption on the authority, responsibility, and role of the notary as a public official. This study employs normative legal research with a statutory approach, a conceptual approach, and a comparative law approach. The results indicate that smart contracts are conceptually categorized as agreements, provided they fulfill the validity requirements as stipulated in Article 1320 of the Civil Code (Kitab Undang-Undang Hukum Perdata). However, the necessary legal framework requires harmonization between the Civil Code, the Notary Office Act, and the Electronic Information and Transactions (EIT) Act, including regulations on electronic signatures and digital certificates to ensure legal certainty and protection. The novelty of this study lies in its conceptualization of the notary as a “digital gatekeeper” who bridges the automated, immutable “code-is-law” mechanism with the qualitative, subjective requirements of civil law (such as free will and legal capacity) which algorithm-driven systems inherently lack. The implementation of smart contracts does not eliminate the notary’s authority; rather, it fosters a transformation of the notary’s role from a mere deed-maker to a guardian of legal legitimacy for digital transactions. Notaries retain the fundamental authority to ensure the fulfillment of legal requirements for agreements and to provide both preventive and repressive legal protection for the parties involved. This study contributes scientifically by offering a synchronized regulatory model rooted in Progressive Law theory, serving as a conceptual blueprint for future civil law legislative reforms in mitigating blockchain disruption. Consequently, integrating smart contracts into notarial practice necessitates regulatory updates capable of bridging the principle of deed authenticity with digital technological advancements to guarantee legal certainty, justice, and utility in the digital era.